The relationship between concentration of the banking sector in Poland and its soundness - Karolina Wójcicka (e-Finanse: Financial Internet Quarterly, 2016)
Each year assets of the banking sector in Poland increase and thereby its significance in the real economy increases as well. At the same time, the ongoing consolidation process and changes in the ownership structure cause the Polish banking sector to play a substantial role not only on the local financial market, but on the European market as well and Polish banks are becoming more and more significant entities in their international banking groups (both in Europe and worldwide). However, the perspective of concentration increase and restriction of the Polish banking sector to a few operating banks (dominated by entities with foreign capital) is a source of distress in the context of its soundness - and due to its significance in the Polish economy - to the whole financial sector and real economy. The main goal of this article is to analyse the changes of concentration in the banking sector in Poland, including the ownership concentration, while attempting to determine its soundness (using the financial stability ratios method) The purpose of the study is also to prove a thesis that limited concentration with diversification of the ownership structure and its limited concentration favours thesoundness of a banking system. The study was carried out on the basis of an analysis of literature (both Polish and English) and comparative analysis (of the concentration of the Polish banking sector against other European countries). Qualitative analysis was complemented with quantitative research, based on analysis of statistical data.
Keywords: F65; G15; G21; G32; 330; banking sector concentration; Polish banking sector; financial soundness; financial stability; ownership structure; foreign capital